Ring Closure Reaction Pathway of a Diarylethene in Solution Using Femtosecond Time‐resolved Fluorescence Spectra. (14th February 2019) - Seo, Kiho; Eom, Intae; Shim, Sangdeok; Kim, Chul Hoon; Joo, Taiha
Abstract : Photochromic ring closure reaction dynamics of 1, 2‐bis(2‐methylbenzo[ b ]thiophene‐3‐yl)hexafluoro cyclopentene is investigated by means of time‐resolved fluorescence spectra. Compared with a single wavelength probe, direct measurement of the emission spectra during the reaction provides unambiguous and straightforward picture for the ring closure reaction pathway. We observe two different emission bands in the fluorescence of the open ring isomer. From the global analysis for the spectra, we obtain <1 ps time constant for the ring closure reaction in polar solvent. Moreover, the ring closure reaction of the compound takes place entirely on the ultrafast timescale. The unreactive parallel conformer decays to the ground state by 150 ps time constant. Abstract :